Parcelamento da dívida exequenda - Puglia, Fabiana Ferraresi (2015)
The present paper intends to clarify the legal nature of splitting the execution debt into installments as forecasted in Article 745-A of the Brazilian Civil Procedure Legislation (Código de Processo Civil), added by Law No. 11.382 dated as of December 6th, 2006, presenting its controversial aspects – such as the requirement of creditor’s acquiescence for its approval; its subsidiary applicability in the court decision execution procedure and its applicability before the Special Civil Court (Juizado Especial Cível), presenting the provision in light of the new Brazilian Civil Procedure Legislation of 2015 (Código de Processo Civil de 2015)